Об артикуляционном аспекте представления русской звуковой системы русистам-инофонам - Борисовна Лихачева, Алла (Slavistica Vilnensis, 2010)
The article asserts that the presentation of Russian phonetic system which is addressed to non-native students of Russian philology should have some important distinctions from the one devoted to university students in Russia. Specifically, the phonetic course for Lithuanian students of Russian philology must not only rest upon the classification parameters of Russian sounds, but also apply more efficiently the elements of the contrastive analysis of both languages’ phonetic systems. In addition, some concepts of general phonetics, such as articulatory goal and articulatory gesture, must be used. It seems to be expedient for theoretical aims as well as practical, because the adoption of linguistic data of this kind helps to shape and support the correct Russian articulatory habits.